(untitled) (Research, Society and Development, 2026)
Objective: to report the experience of nursing residents in developing practical guides as a strategy for providing guidance on enteral tube care to patients and companions in cardiology inpatient units. Method: This is an experience report carried out in December 2026 in two inpatient units: adult and pediatric, at a tertiary hospital specializing in cardiology, located in the city of São Paulo. The experience was carried out by nursing residents. Results: Initially, a situational diagnosis was performed considering the profile of the target audience and its sociocultural context. The practical guides were developed based on Contextualized Instructional Design, covering the stages of defining the profile and theoretical framework and basing them on guidelines and manuals. The practical guides will be presented by the nurse in charge, with the aim of enabling the patient and their companion to understand the importance of enteral tube care. Conclusion: With the implementation of the practical guides in each of the inpatient units, the importance of the process being developed based on co-responsible care was observed. These materials not only facilitate the understanding of health guidelines by patients and companions, but also promote greater engagement and active participation in care.